DEFERRED REVOLUTION. TO THE NOVEL BY MICHAEL DOUBEK INADAPTABILITY - Vaníček, Jakub (Bohemica Olomucensia, 2020)
Michael Doubek's novel was awarded by the Union of Czech Writers as the prose of 2017. In my contribution I offer an interpretation of Doubek's novel, which takes into account the closure of this work in the circle of related writers. Through the concept of Louis Althusser (ideological interpellation), I try to show how the characters of this novel try to break free from the post-capitalist, dystopian world and penetrate into a new, liberated reality.
Keywords: Michael Doubek; Unie českých spisovatelů; Louis Althusser; postmarxism; ideology; ideological apparatuses; contemporary Czech literature